Tantangan Penerapan Etika Jurnalistik pada Media Online di Indonesia - Fitrianingsih, Ine; Salma, Qanitah; Sartika, Rini; Nashrudin, Achmad (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study examines ethics as a fundamental guideline in life and the journalism profession, particularly in response to the dynamics of digital media. Ethics is understood as a commitment to doing the right thing, even when the temptation to act unethically is stronger. Ethics is closely related to morality, is contextual in nature, often exists in gray areas, and evolves alongside technological and social change. In journalistic practice, the Journalistic Code of Ethics serves as a primary reference for maintaining independence, professionalism, accuracy, source protection, and integrity. However, online media face serious challenges, including clickbait practices, inadequate fact-checking, the spread of disinformation, and pressures from algorithms and traffic-based business models. These conditions risk shifting ethical values in favor of speed and content popularity. Moreover, existing regulations have not fully addressed the complexities of digital journalism. This research adopts a descriptive qualitative approach through literature review and conceptual analysis of digital journalistic practices. The findings indicate that the Journalistic Code of Ethics needs to be updated and strengthened to remain relevant within the digital media ecosystem. Such adaptation is essential to ensure journalism continues to fulfill its social responsibility, maintain public trust, and uphold truth amid the rapid and massive flow of information.